1999
DOI: 10.1042/cs0960041
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertension increases vasoconstrictor responsiveness of rat aorta

Abstract: We have examined the effects of pre-hepatic portal hypertension on the responsiveness of aorta from Wistar and Sprague-Dawley rats. Rats were made portal hypertensive by creating a calibrated portal vein stenosis, or sham operated. In rat aorta, there was no significant difference between portal hypertensive and sham-operated animals in the contractile potency of KCl, noradrenaline or phenylephrine. In aortas from Wistar rats, the maximum response to KCl (0.71+/-0.12 g) and noradrenaline (1.00+/-0.17 g) but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For instance, in portal-veinligated rats, different laboratories have found that the mesenteric vessels show a hyporesponsiveness to vasoconstrictors [4,[7][8][9], but several papers agree that the aorta shows a normal response [23]. However, in cirrhotic rats with ascites, hyporesponsiveness to vasoconstrictors has been found in several vessel types [6,8,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in portal-veinligated rats, different laboratories have found that the mesenteric vessels show a hyporesponsiveness to vasoconstrictors [4,[7][8][9], but several papers agree that the aorta shows a normal response [23]. However, in cirrhotic rats with ascites, hyporesponsiveness to vasoconstrictors has been found in several vessel types [6,8,[24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%